Studi Sistem Tanam Jajar Legowo terhadap Peningkatan Produktivitas Padi Sawah - Misran Misran (Jurnal Penelitian Pertanian Terapan, 2014)
The studies of row planting system â€œlegowoâ€ to the increased productivity of lowland rice. This research aims to determine the best planting system in order to obtain optimum growth and yield. The experiment site in lowland farmers Piruko Sitiung, Dharmasraya district, West Sumatra, from May to September 2009. The research using a randomized block design (RBD) with 4 replications and 5 treatments planting systems, namely: (A) the Row â€œLegowoâ€ 2:1, (B) the Row â€œLegowoâ€ 4:1, (C) the Row â€œLegowoâ€ 6:1, (D) the Row â€œLegowoâ€ 8:1, and (e) Without the Row â€œLegowoâ€ Control. Fertilizers are used ; 200 kg Urea, 100 kg SP36, and 50 kg KCl/ha. Urea and KCl are given three times with brocasting system at 1, 4 , and 7 weeks after planting (wap), while the SP36 is given at 1 wap combined with Urea and KCl. The seeds used Batang Piaman variety planted three seedling per hill, spacing of 25x25 cm . Data were collected on; plant height , maximum number of tillers/hill, number of productive tiller/hill, yield components, and yield. The results showed that â€œlegowoâ€ row planting system significantly affect the agronomic component plants, except at plant height. Against the yield components and the results also showed a marked influence on the percentage of empty grains unless and 1000 grain weight. â€œLegowoâ€ row planting system can increase the yield of dry grain harvest around 19.90 to 22%. This experiment suggests that in order to obtain optimum productivity of lawland rice is recommended to use of â€œLegowoâ€ row planting system. Keywords : â€œLegowoâ€ row planting system, productivity, lawland rice.